Application and Validation of an Existing Industry 4.0 Guideline for the Development of Specific Recommendations for Implementation - Bogner, Eva; Abersfelder, Sandra; Heyder, Andreas; Franke, Jörg (Advanced Materials Research, 2016)
From a technological point of view Industry 4.0 is already at an advanced stage. However, it still needs time to implement aspects of Industry 4.0 into the everyday life of project work. A major cause is the lack of methodologies in this area. Production-related areas must be prepared to identify the requirements and needs of Industry 4.0, right from the planning phase of the project. This paper describes an approach to create an Industry 4.0 Project-Roadmap as a base of important strategical decisions. Using the VDMA industry 4.0 toolbox, innovative ideas are developed, structured and finally prioritized considering effort and costs. The result is a roadmap, which allows the design of basic Industry 4.0 equipment of the project as well as to integrate further features as options. Due to different target groups and a very specific expectation the workshop procedure is modified to the already by the VDMA published guideline and presented in detail below.
Keywords: Coordination; Product development; Guideline

Comparison analysis of the magnetic field and the magnetic force inside of an electromagnetic actuator with the use of an armature measuring sensor - Heyder, Andreas; Losch, T.; Meyer, Alexander Wilhelm; Abersfelder, Sandra; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
Common errors in electromagnetic actuators must be reduced in order to meet the increasing requirements in quality and manufacturing costs. In-line magnetic process control is a promising method to avoid a great number of errors in early stages of production. This paper displays the meaningful correlation between the magnetic field and magnetic force characteristics of a proportional magnet. For this investigation, an armature measuring sensor is developed and implemented into a magnetic field test bench, which enables the realization of a so called smart factory.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electromagnetic actuator; in-line measurement; magnetic process control; three-dimensional magnetic field measurement

Concept for Magnet Intra Logistics and Assembly Supporting the Improvement of Running Characteristics of Permanent Magnet Synchronous Motors - Meyer, Alexander Wilhelm; Heyder, Andreas; Kühl, Alexander; Sand, Christian; Gehb, Hermann; Abersfelder, Sandra; Franke, Jörg; Holzhey, Rocco; Buettner, Ulrich; Wangemann, Sebastian (Procedia CIRP, 2016)
Current scientific studies prove the dependency of the running characteristics of permanent magnet synchronous motors on variations of the physical properties of permanent magnets and manufacturing errors. Currently, this fact is not considered in most process chains for magnet and rotor assembly. Thus, insufficient rotor quality can only be detected during the end-of-line test, causing rejects of whole motors. As a solution for these drawbacks, a computerized magnet intra-logistics storage and assembly concept is presented, using sophisticated magnet measurement technologies. This concept allows for the traceability of single magnets and enables to compensate variations of the magnetic properties by selective magnet assembly.
CRIS-Team Scopus Importer:2023-03-07
Keywords: magnet assembly; magnetic tolerancing; PMSM; tolerancing; traction drives

Contribution to the Reduction of Annealing Processes in the Manufacturing of Valve Solenoids by Using Inline Measuring Technology in the Caulking Process - Freiherr von Lindenfels, Johannes; Heyder, Andreas; Funk, Stefan; Pigler, Stefan; Franke, Jörg (Energy Efficiency in Strategy of Sustainable Production IV, 2018)
Electromagnetic actors (solenoids) are used in automotive and automation technology as valve actors for pneumatics and hydraulics or as actuating and pressure solenoids. During assembly there are often press-in and caulking processes used. A central quality aspect of the final control elements is the adherence to defined actuating force ranges in order to ensure the switching process and at the same time to keep wear within limits. These defined force ranges can currently only be maintained by additional heat treatment of the parts. The hysteresis of the assembled unit can be influenced by the caulking. The objective of this paper is to propose the potential reduction of annealing processes by revealing the interdependencies between the magnetic interactions of the individual components and the assembly process parameters. In addition, errors in the caulking process are detected and prevented at an early stage. A magnetic characterization of the soft magnetic components and assemblies before and during their assembly is proposed. Furthermore, the integration of the measurement data into a process control system is intended. The precondition is the development and construction of measuring equipment and systems that can be used to assess the magnetic properties at an early stage of assembly. The assembly can then be adjusted in order to compensate batch fluctuations. As a consequence new materials can be used to eliminate complex annealing processes prior to assembly. <br
Keywords: Caulking; Hall Sensor; Inline Measuring Technology; Solenoids

Crack detection in PM-rotors using magnetic field measurement and data processing - Abersfelder, Sandra; Meyer, Alexander Wilhelm; Heyder, Andreas; Herzog, Moritz; Franke, Jörg; Brela, Matthaeus (2017 7th International Electric Drives Production Conference, EDPC 2017 - Proceedings, 2018)
Electric drives efficiency is determined by the mechanical and magnetic properties of the functional elements stator and rotor. Focus element for this investigation is the rotor including its permanent magnets. Due to several manufacturing influences the properties of those magnets vary considerably. Magnet failures that can occur during manufacture are cracks, blowholes or inclusions, which can lead to commutation problems or to increased noise [1]. Crack propagation is a long-lasting process and cause unintentional failure in field. Currently no automated quality inspection of micro cracks is available in electric drive production. Consequently, the challenge is to develop reliable and safe process concept, to separate bad from good rotors based on magnetic field measurements in order to detect failures at the internal or external assembled magnets. For this purpose, a data analyzing method was developed to identify and characterize micro cracks in already assembled permanent magnets.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Actuators and System Integration; Crack Detection; Data Processing; Fault Detection; Magnetic Field Measurement; Permanent Magnet; Sensors

Fully automated rotor inspection apparatus with high flexibility for permanent magnet synchronous motors using an improved hall sensor line array - Meyer, Alexander Wilhelm; Heyder, Andreas; Brela, Matthäus; Urban, Nikolaus; Sparrer, Johannes; Franke, Jörg (5th International Conference on Electric Drives Production, EDPC 2015, 2015)
As a result of the market expansion of permanent magnet synchronous motors due to the increasing demand for high-performance drives for a wide range of applications such as traction drives for electric mobility, positioning drives for machine tools as well as high-precision drives for special-purpose machines and the quality demands involved, in-line capable measurement technology is needed. Thus in the area of electric drives manufacturing the rejection rate is required to be reduced by early fault detection. This can be achieved by measuring the rotor excitation field created by permanent magnets prior to the assembly of rotor and stator. In this Paper an apparatus for fully automated inspection of both internal and external rotors within a wide range of dimensions is presented. This is done with the aid of a one dimensional Hall-Sensor line array, which is manufactured with high accuracy and the use of an open source CNC system. The presented device is capable for in-line operation at the end of the rotor assembly process chain to detect possible magnetization and assembly faults prior to the final assembly of the electric drive by visualization of the rotor excitation field.

Magnetic stray field measurement of magnetic specimen - Heyder, Andreas; Tenner, M.; Meyer, Alexander Wilhelm; Abersfelder, Sandra; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
The production of electromagnetic actuators is a complex procedure with a great number of potential influences on the process and hence the quality of the final product itself. The necessity for an in-line magnetic production system which allows an efficient monitoring of the magnetic properties of work pieces at different stages of the production process thus becomes apparent.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electromagnetic actuator; in-line measurement; magnetic process control; magnetic stray field measurement; test bench development; three-dimensional magnetic field measurement

Optimization of a servo motor manufacturing value stream by use of 'Industrie 4.0' - Abersfelder, Sandra; Heyder, Andreas; Franke, Jörg (2015 5th International Conference on Electric Drives Production, EDPC 2015 - Proceedings, 2015)
'Industrie 4.0' establishes multidirectional ways of cross-linking in the production area. Therefore, a complex integration of horizontal and vertical interactions has to work hand in hand. A closer look into present production shows a huge amount of optimization potentials on the way to a 'Smart Factory' with high product variability. Hence, one of the next milestones for production is to create a virtual image of the real products in the manufacturing execution system (MES) in order to have a gapless traceability and an extensive storage of process data along the whole value chain. Especially data mining will gain importance to scan information for meaningful correlations or creating configuration rules as well as decisions for subsequent process steps. For a servo motor production the implementation of a magnetic field measurement of rotors is an opportunity to gather data for data mining. In addition to that, other interesting benefits are expected in failure detection, quality improvement and an increase in performance. To evaluate the different mentioned areas of activity, a pilot test series is planned. It will also provide data sets for a first data mining investigation. The concept of the first rotor measurement test procedure is presented in the following.
CRIS-Team Scopus Importer:2023-03-07
Keywords: 'Industrie 4.0'; Magnetization; Servo Motors

Prediction of electric motor performance by in-line testing of permanent excited rotors - Abersfelder, Sandra; Meyer, Alexander Wilhelm; Heyder, Andreas; Thanner, Marius; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
The market growth of electric drives is pushed forward due to high coercive magnet material and new, more efficient motor designs. These new designs require only small tolerances within the whole manufacturing process. While quality assurance is well established within the stator manufacturing process, the rotor assembly process suffers from lack of testing. Hence, this gap causes rejects not detected until the end-of-line-test of the whole motor, measuring especially the back electromotive force (BEMF) and the total harmonic distortion (THD) of the output signal. To avoid rejects of whole motors at the end of the value chain, this paper presents the possibilities delivered by in-line magnetic field measuring of the rotor. Therefore, different testing methods, such as a commercial available monolithic hall array and a discrete hall line array are used and evaluated. Out of these measurement series a rotor KPI is defined in order to evaluate the rotor quality right after the measurement.
CRIS-Team Scopus Importer:2023-03-07
Keywords: BEMF; hall measurement; manufacturing tollerances; permanent magnet; synchronous motor

Use of automated in-line capable magnetic stray field measurement method for monitoring the value chain quality of magnetic circuits - Brela, Matthäus; Heyder, Andreas; Dietlein, Fabian; Markert, Johannes; Franke, Jörg; Hauenstein, R.; Wagner, R. (2014 International Symposium on Power Electronics, Electrical Drives, Automation and Motion, SPEEDAM 2014, 2014)
Common defects in electromagnetic actuators due to the manufacturing process are heterogeneous magnetic properties of the materials, cracks and defects in the magnetic materials and parasitic air gaps in and directly around the magnetic circuit. In most cases the error cause can be found in the value chain and is caused by material handling, assembling tolerances, environmental influences, etc. Considering the high global cost pressure, test systems must be adapted to the increasing complexity of the components in order to be able to detect defects completely in-situ and have smallest possible amortization period. For these requirements the novel and nondestructive measurement system is suitable to monitor and assure quality of magnetic actuators within the manufacturing process. The measuring principle is the characterization of electromagnetic actuators according to the detection of magnetic stray fields outside the magnetic circuit and the magnetic useful field inside the actuator that can be quantified by magnetic sensors. The intensity of the magnetic stray fields depends on the magnetic flux density and flux distribution in the magnetic circuit. Permeability variations for example caused by air gaps or internal stresses influence the flux distribution. In most cases they are caused by process parameter variations of the manufacturing and assembling. With the developed method this influences can be detected in an early stage of the manufacturing process automatically and in-line. This can lead to more competitiveness and long-term viability of the location. © 2014 IEEE.
CRIS-Team Scopus Importer:2023-03-07